Pengaruh System Quality dan Perceived Usefulness terhadap Continuance Intention Aplikasi LINE dengan Satisfaction sebagai Mediator - Muhamad Aqdi Alhamro; Munawaroh Munawaroh; Fauzan Fadlullah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of communication technology and the high level of social media usage in Indonesia have intensified competition among instant messaging applications in retaining users. Although LINE was once one of the most popular applications, in recent years there has been a decline in the number of active users, which is believed to be influenced by the removal of several key features, a decrease in perceived usefulness, and various complaints related to system quality. The condition raises questions regarding the factors that influence users’ intentions to continue using the LINE application on an ongoing basis. This study aims to analyze the effect of System Quality and Perceived Usefulness on the Continuance Intention of the LINE application, with Satisfaction acting as a mediating variable. A quantitative approach was employed through an online survey involving 200 respondents in Jakarta who had used LINE for at least the past year. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that system quality and perceived usefulness have a positive and significant effect on satisfaction. Furthermore, perceived usefulness and satisfaction have a positive and significant effect on continuance intention. However, system quality is proven to have no significant effect on continuance intention. The indirect effect findings indicate that satisfaction significantly mediates the relationship between system quality and perceived usefulness on continuance intention.